2015
DOI: 10.1037/pas0000048
|View full text |Cite
|
Sign up to set email alerts
|

How reliable are Psychopathy Checklist–Revised scores in Canadian criminal trials? A case law review.

Abstract: The Psychopathy Checklist-Revised (PCL-R;Hare, 2003) is a professional rating scale that enjoys widespread use in forensic and correctional settings, primarily as a tool to inform risk assessments in a variety of types of cases (e.g., parole determinations, sexually violent predator [SVP] civil commitment). Although widely described as "reliable and valid" in research reports, several recent field studies have suggested that PCL-R scores provided by examiners in forensic cases are significantly less reliable t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
65
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 51 publications
(76 citation statements)
references
References 58 publications
8
65
2
Order By: Relevance
“…More frequently, however, the written decision provided little context and explanation for how, if at all, the court factored this testimony into the final opinion, a finding consistent with previous case law reviews (e.g., DeMatteo & Edens, 2006;Edens et al, 2015). We echo the suggestion of DeMatteo et al (2014) that a comprehensive review of trial transcripts from various geographic regions may provide additional, more robust, data as to how these measures are used in criminal proceedings and how much attention is given to the measures and mental health testimony by the court.…”
Section: Limitations and Directions For Future Researchsupporting
confidence: 65%
See 2 more Smart Citations
“…More frequently, however, the written decision provided little context and explanation for how, if at all, the court factored this testimony into the final opinion, a finding consistent with previous case law reviews (e.g., DeMatteo & Edens, 2006;Edens et al, 2015). We echo the suggestion of DeMatteo et al (2014) that a comprehensive review of trial transcripts from various geographic regions may provide additional, more robust, data as to how these measures are used in criminal proceedings and how much attention is given to the measures and mental health testimony by the court.…”
Section: Limitations and Directions For Future Researchsupporting
confidence: 65%
“…This coding form was modeled after forms used in previous case law reviews (DeMatteo et al, ; Edens et al, ) while including items pertinent to the present research question. Coding was completed by two doctoral‐level psychologists and three doctoral graduate students.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Perhaps foremost, a growing body of field literature (see Edens & Boccaccini, ) suggests that scores from this instrument are not particularly reliable in applied contexts in which mental health experts are introducing them. Although the professional manual (Hare, ) provides intraclass correlation (ICC) statistics across various offender samples in the 0.85 and above range, numerous field studies have suggested that it may be closer to 0.60 (or even lower) in adversarial forensic settings (e.g., Edens, Cox, Smith, DeMatteo, & Sörman, ; Miller, Kimonis, Otto, Kline, & Wasserman, ). Of particular concern, the aforementioned Factor 1 traits seem to be even less reliable, producing field results in which sometimes more than half the variance in scores is the result of some form of error (Miller et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Mental health professionals frequently use psychopathy in their assessments when assessing risk of violence (Hurducas, Singh, de Ruitner, & Petrila, 2014;Singh, Bjørkly, & Fazel, 2016;Viljoen, McLachlan, & Vincent, 2010). Psychopathy is often used in a variety of court cases (e.g., parole determinations, sexually violent predator civil commitments) and particularly in violent cases where a dangerous offender label is in question Edens, Cox, Smith, DeMatteo, & Sörman, 2015).…”
Section: List Ofmentioning
confidence: 99%